Evaluación de la inyección alternada de agua-polímero como método de recobro mejorado en un yacimiento de crudo pesado con baja permeabilidad mediante la herramienta CMG (2021)
Throughout history, the implementation of an injection system (secondary recovery) is used to improve the production efficiency of a well when the primary production systems become obsolete, this in order to improve the efficiency of oil sweep that remains trapped in the formation. This degree project seeks to evaluate the potential of alternate water-polymer injection as an improved recovery method, using a synthetic model and proposing various injection scenarios. The software used to obtain the model and run the scenarios was CMG (Computer Modeling Group). The model corresponds to a medium with low permeability, highly heterogeneous, low production, high percentage of remaining and residual oil. It was found that the maximum recovery factor for alternate water-polymer injection was 23.34%, surpassing by only 0.81% the second-best scenario corresponding to continuous water injection. Finally, a sensitivity analysis of the alternating water-polymer injection is carried out, establishing that the optimal parameters are an injection flow rate of 5000 m3 / day, polymeric concentration of 1500ppm, polymeric viscosity of 10 cp, alternation in injection periods between 2 months. and 3 months.